Pengembangan Produk Kopi Herbal Berbasis Rempah Lokal Sebagai Strategi Peningkatan Daya Saing Usaha Mikro di Kabupaten Jember - Ali, Fandyka Yufriza; Nugroho, Setyo Andi; Fatimah, Titien; Asmono, Sepdian Luri; Rosdiana, Eva; Pratita, Dian Galuh; Firgiyanto, Refa (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2025)
Indonesia is one of the world’s largest producers of coffee and spices; however, the integration of these resources into innovative MSME products remains limited. Jember Regency, known as a center of robusta coffee and a producer of spices such as ginger, cardamom, and cinnamon, holds great potential that has yet to be fully utilized by micro-enterprises. This program aimed to enhance the competitiveness of coffee-based MSMEs through herbal coffee innovation training. The method used was a participatory-educational approach, consisting of a pretest, theoretical presentations, hands-on roasting and blending practice, organoleptic testing, and final evaluation. Participants were drawn from MSME actors and coffee farmer communities in the Jember area. Results showed a significant cognitive improvement, with average scores increasing from 36 to 80 (a 122% increase). Participants also showed improved hardskills in herbal coffee formulation, label design, and digital marketing. A blend of 10% ginger and 5% cardamom was rated highest in taste tests. This activity demonstrates that local resource-based interventions can effectively improve product competitiveness and MSME self-sufficiency.